PEMANFAATAN PASIR SEBAGAI MATERIAL PEMBUATAN KERAMIK SISWA SMK NEGERI 2 SUKAWATI - Noor Azreena Malik; Ni Made Rai Sunarini; Mercu Mahadi (Hastagina : Jurnal Kriya Seni, 2022)
Teaching asistency activities in the State High School 2 Sukawati with the material "Utilization of Sand as Ceramic Material Making Class Xii Kriya Ceramics" aims to foster creativity, innovation and initiative from students in creating new ceramic works because based on observations from the authors of the work produced is still monotonous with form, material, same decoration and coloring. In addition to developing the potential for ceramic xii craft students in creating works, this teaching asistency activity has a focus on an experiment in the use of sand material.  The results of this experiment are expected to provide references in increasing the educational cauldron in other practical learning processes as well as schools can support teachers to create more varied media to produce more innovative work. can make it easier for teachers to further enhance the creativity and innovation of the work of students. In this activity the author uses qualitative methods, data collected through interviews, observations, and document studies and uses experimental demonstration learning methods for the development of student-splifting creativity. It was concluded that using experimental demonstration methods applied to students produced quite good results. The use of soil mixed with black sand has good results based on the work students make in the form of vases and sugar holders.